Ruthenium-doped Z-type hexaferrite

JP7637118B2Active Publication Date: 2025-02-27ROGERS CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022506817
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-05
Filing Date
2020-07-28
Publication Date
2025-02-27
Estimated Expiration
2040-07-28

Smart Images

  • Figure 0007637118000008
    Figure 0007637118000008
  • Figure 0007637118000009
    Figure 0007637118000009
  • Figure 0007637118000010
    Figure 0007637118000010
Patent Text Reader

Abstract

In one embodiment, the ferrite composition has the formula: (Ba 3-x M x )Co2(M'Ru) y Fe 24-2y-z O 41 wherein M is at least one of Sr, Pb, or Ca; M' is at least one of Co, Zn, Mg, or Cu; x is 1 to 3; y is greater than 0 to 2; and z is -4 to 4. In another embodiment, an article includes a ferrite composition. In yet another embodiment, a method of making a ferrite composition includes mixing ferrite precursor compounds including Fe, Ba, Co, and Ru; and sintering the ferrite precursor compounds in an oxygen atmosphere to form Ru—CoZ ferrite.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 882,681, filed August 5, 2019, which related application is incorporated herein by reference in its entirety. [Background technology]

[0002] Improved performance and miniaturization are needed to meet the ever-increasing demands of devices used in ultra-high frequency (UHF), L-band and S-band applications, especially in various commercial and defense-related industries. Miniature antenna elements are constantly being developed as key components of radar and modern wireless communication systems. However, developing ferrite materials for use in such short-wave applications has been difficult because most ferrite materials exhibit relatively high magnetic losses at short waves. In general, hexagonal ferrites or hexaferrites are a type of iron oxide ceramic compound that has a hexagonal crystal structure and exhibits magnetic properties. Z-type ferrite, Ba3Me2Fe 24 O 41 and Y-type ferrite, Ba2Me2Fe 12 O 22 Several families of hexaferrites are known, including M-type ferrites ((Ba,Sr)Fe 12 O 19 ), W-type ferrite ((Ba,Sr)Me2Fe 16 O 27 ), X-type ferrite ((Ba,Sr)2Me2Fe 28 O 46 ) and U-type ferrite ((Ba,Sr)4Me2Fe 36 O 60 ) are mentioned. Summary of the Invention [Problem to be solved by the invention]

[0003] Some hexaferrites, such as cobalt-substituted barium Y-type (Co2Y) and Z-type (Co2Z) hexaferrites, can have much higher ferromagnetic resonance frequencies and permeabilities compared to spinel ferrites, making them suitable for shortwave applications. Despite these improvements, these substitutions also increase magnetic losses, limiting their use in shortwave and microwave devices. Although Z-type ferrites are candidates for high impedance magneto-dielectric composites, high magnetic losses limit their use. Therefore, improved Z-type ferrites are desirable. [Means for solving the problem]

[0004] Disclosed herein is a ruthenium doped Z-type hexaferrite.

[0005] In one embodiment, the ferrite composition has the formula (Ba 3-x M x )Co2(M'Ru) y Fe 24-2y-z O 41 (wherein M is at least one of Sr, Pb, and Ca; M' is at least one of Co, Zn, Mg, and Cu; x is 1 to 3; y is greater than 0 and up to 2; and z is -4 to 4).

[0006] In another aspect, an article includes at least one of a ferrite composition or a ferrite composite.

[0007] In yet another embodiment, a method of making a ferrite composition includes mixing ferrite precursor compounds including Fe, Ba, Co, and Ru; and sintering the ferrite precursor compounds in an oxygen atmosphere to form Ru-Co2Z ferrite.

[0008] These and other features are illustrated by the following figures, detailed description and claims.

[0009] The following figures are exemplary embodiments, which are provided to illustrate the present disclosure. The figures are illustrative of examples, and are not intended to limit devices made according to the present disclosure to the materials, conditions, or process parameters shown therein. [Brief description of the drawings]

[0010] [Figure 1] 1 is a graphical representation of magnetic permeability and magnetic loss tangent with frequency for Examples 1, 2, 4 and 6. [Diagram 2] 1 is a graphical representation of magnetic permeability and magnetic loss tangent with frequency for Examples 3, 5 and 7. [Diagram 3] 1 is a graphical representation of magnetic permeability and magnetic loss tangent with frequency for Examples 4, 6 and 8. [Figure 4] 1 is a graphical representation of dielectric constant and dielectric loss tangent with frequency for Examples 4, 6 and 8. [Diagram 5] 1 is a graphical representation of magnetic permeability and magnetic loss tangent with frequency for Examples 9 and 10. [Figure 6] 1 is a graphical representation of dielectric constant and dielectric loss tangent with frequency for Examples 9 and 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] It has been discovered that replacing at least a portion of the iron ions in Z-type hexaferrite with ruthenium can result in Ru-Co2Z ferrite with improved properties. Specifically, Ru-Co2Z ferrite has the general formula: (Ba 3-x M x )Co2(M'Ru) y Fe 24-2y-z O 41 (In the formula, M is at least one of Sr, Pb, and Ca; M' is at least one of Co, Zn, Mg, and Cu; x is 1 to 3; y is greater than 0 and 2, or 0.001 to 2; and z is -4 to 4.) M' can be Co. The ratio of Ru to M' can be from 0.01 to 3, or from 0.01 to 1. The variable z can be varied to be non-zero to include non-stoichiometric formulations.

[0012] The Ru-Co2Z ferrite may have an easy magnetization plane (c-plane). The Ru-Co2Z ferrite may be suitable for use as an antenna or inductor at SL band frequencies by having at least one of high permeability, high operating frequency, or low magnetic loss. The Ru-Co2Z ferrite, in solid ceramic form, may have a permeability of 3.5 or more, or 5 or more, or 5-10, at frequencies of 1-2 gigahertz, or 2-4 gigahertz. The Ru-Co2Z ferrite, in solid ceramic form, may have a magnetic loss tangent tanδ of 0.4 or less, 0.2 or less, or 0.1 or less, or 0.08 or less, or 0.04-0.4, at frequencies of 1-2 gigahertz. μ The Ru-Co2Z ferrite, in its solid ceramic form, may have a dielectric constant of 6 to 15, or 6 to 12, or 10 to 14 at frequencies of 1 to 2 gigahertz. The Ru-Co2Z ferrite, in its solid ceramic form, may have a dielectric loss tangent tanδ of 0.15 or less, or 0.009 or less, or 0.008 or less, or 0.002, or 0.001 to 0.15 at frequencies of 1 to 2 gigahertz. ε The Ru-Co2Z ferrite, in solid ceramic form, may have an operating frequency of 0.1 to 4 gigahertz, or 0.5 to 2 gigahertz, or 1 to 2 gigahertz.

[0013] Ru-Co2Z ferrite has a low dielectric loss tangent tanδ in the ultra-high frequency range. ε or magnetic loss tangent tanδ μ For example, Ru-Co2Z ferrite, in the form of a solid ceramic, may have a dielectric loss tangent tanδ of 0.01 or less, or 0.008 or less, or 0.006 to 0.01 at frequencies of 1 to 2 gigahertz. ε , or 0.12 or less, or 0.08 or less, or a magnetic loss tangent tanδ of 0.05 to 0.12 μ The present invention may have at least one of the following:

[0014] As used herein, the magnetic and dielectric properties are measured in a coaxial antenna by a Vector Network Analyzer (VNA) using the Nicholson-Ross-Weir (NRW) method, and the permeability and permittivity values ​​are relative permeability and relative permittivity, respectively.

[0015] The Ru-Co2Z ferrite can be prepared using any suitable method. In general, the Ru-Co2Z ferrite may be formed by first forming a mixture including precursor compounds including oxides of at least Ba, M, Co, Ru, and Fe, where M is at least one of Sr, Pb, or Ca. For example, the mixture may include at least BaCO3, MCO3, Co3O4, RuO2, and Fe2O3. The mixture may include 5 to 20 weight percent BaCO3, based on the total weight of the mixture. The mixture may include 5 to 50 weight percent MCO3, based on the total weight of the mixture. The mixture may include 2 to 15 weight percent Co3O4, based on the total weight of the mixture. The mixture may include 0.1 to 10 weight percent RuO2, based on the total weight of the mixture. The mixture may include 50 to 80 weight percent Fe2O3, based on the total weight of the mixture. The mixture may further include an oxide of at least one of Zn, Mg, or Cu. It should be noted that the mass percentages of the mixture may be relative to the total mass of the oxides in the mixture.

[0016] The mixture can be calcined in air to form ferrites, including Z-type ferrites. Calcination can be performed at a calcination temperature of 800 to 1,300 degrees Celsius (°C). Calcination can be performed for a calcination time of 0.5 to 20 hours, 1 to 10 hours, or 2 to 5 hours. It is noted that the calcining step is optional and the only heating step may be the sintering step to form the ferrite.

[0017] The ferrite can be ground and optionally sieved to form granules. The sieving step can include sieving through a 10-100 mesh screen. The coarse particles can be further ground to reduce particle size. The fine particles can have a median D50 volumetric particle size of 0.5-50 micrometers, or 0.5-10 micrometers. The particle size can be determined using a Horiba LA-910 laser light scattering PSD analyzer, or as determined in accordance with ASTM D4464-15. The ferrite can be mixed with a binder. The binder can include at least one of poly(vinyl alcohol), methyl cellulose, poly(vinyl butyral), poly(ethylene glycol), or poly(alkylene carbonate). The binder can be present in an amount of 8-12 weight percent based on the total amount of ferrite and binder. The binder can facilitate shaping of the ferrite and can be completely burned off during sintering. The cemented ferrite may have a median D50 volume particle size of 10 to 300 micrometers, or 50 to 300 micrometers.

[0018] The ferrite can be optionally molded and sintered to form Ru-Co2Z ferrite. The molding method is not limited and can include at least one of uniaxial pressing, isostatic pressing, casting, pressing, and the like. Pressing can be performed at a pressure of 0.5 to 2 metric tons per square centimeter. Sintering can be performed at a sintering temperature of 1,000 to 1,300°C, or 1,200 to 1,250°C. The temperature can be ramped up and down from the sintering temperature at a rate of 1 to 5°C per minute, each independently. Sintering can be performed for a sintering time of 1 to 20 hours, or 5 to 12 hours. Sintering can be performed in an oxygen environment to help reduce dielectric loss. Oxygen can be introduced into the sintering chamber at a flow rate of 0.1 to 10 liters per minute. The sintered Ru-Co2Z ferrite can be finished in any desired manner, for example, by cutting or polishing, depending on the application.

[0019] An amount of bismuth oxide may be added to the ferrite prior to sintering. The bismuth oxide may be added in an amount of 0.2 to 5 weight percent based on the total weight of the ferrite. The addition of Bi2O3, which may be present at the grain boundaries of the Z-type ferrite phase, may help achieve a composition with equal or substantially equal values ​​of permeability and permittivity while retaining low magnetic and dielectric loss tangents.

[0020] The Ru-Co2Z ferrite may have an average grain size of 1 to 100 micrometers, or 5 to 50 micrometers. The grain size may be measured using at least one of a transmission electron microscope, a field emission scanning electron microscope, or X-ray diffraction.

[0021] The Ru-Co2Z ferrite can be a bulk ceramic or can be present in a composite, for example, including the Ru-Co2Z ferrite and a polymer. The polymer can include a thermoplastic or a thermoset. As used herein, the term "thermoplastic" refers to a material that is plastic or deformable, melts into a liquid when heated, and freezes into a brittle glassy state when cooled sufficiently. Examples of thermoplastic polymers that can be used include cyclic olefin polymers (including copolymers containing polynorbornene and norbornenyl units, e.g., copolymers of cyclic polymers such as norbornene and acyclic olefins such as ethylene or propylene), fluoropolymers (e.g., polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), fluorinated ethylene-propylene (FEP), polytetrafluoroethylene (PTFE), poly(ethylene-tetrafluoroethylene (PETFE) or perfluoroalkoxy (PFA)), polyacetals (e.g., polyoxyethylene and polyoxymethylene), poly(C 1~6 alkyl) acrylates, polyacrylamides (unsubstituted and mono-N- or di-N-(C 1~8Poly(alkyl)acrylamides), polyacrylonitrile, polyamides (e.g., aliphatic polyamides, polyphthalamides, or polyaramids), polyamideimides, polyanhydrides, polyarylene ethers (e.g., polyphenylene ethers), polyarylene ether ketones (e.g., polyether ether ketones (PEEK) and polyether ketone ketones (PEKK)), polyarylene ketones, polyarylene sulfides (e.g., polyphenylene sulfide (PPS)), polyarylene sulfones (e.g., polyether sulfone (PES), polyphenylene sulfone (PPS), etc.), polybenzothiazoles, polybenzenes, Polybenzoxazoles, polybenzimidazoles, polycarbonates (including homopolycarbonates or polycarbonate copolymers, e.g., polycarbonate-siloxane, polycarbonate-ester, or polycarbonate-ester-siloxane), polyesters (e.g., polyester copolymers such as polyethylene terephthalate, polybutylene terephthalate, polyarylate, or polyester-ether), polyetherimides (e.g., copolymers such as polyetherimide-siloxane copolymers), polyimides (e.g., copolymers such as polyimide-siloxane copolymers), poly(C 1~6 alkyl) methacrylates, polyalkylacrylamides (e.g., unsubstituted and mono-N- or di-N-(C 1~8Examples of suitable thermoplastic polymers include polyvinyl alcohols, polyvinyl esters, polyvinyl ether ...

[0022] Thermoset polymers are derived from thermosetting monomers or prepolymers (resins) that can be irreversibly hardened and made insoluble by polymerization or curing, which can be induced by exposure to heat or radiation (e.g., ultraviolet light, visible light, infrared light or electron beam (e-beam) radiation). Thermosetting polymers include alkyds, bismaleimide polymers, bismaleimide triazine polymers, cyanate ester polymers, benzocyclobutene polymers, benzoxazine polymers, diallyl phthalate polymers, epoxides, hydroxymethylfuran polymers, maleimide-formaldehyde polymers, phenols (including phenol-formaldehyde polymers such as novolacs and resols), benzoxazines, polydienes such as polybutadiene (including homopolymers and copolymers thereof, e.g., poly(butadiene-isoprene)), polyisocyanates, polyureas, polyurethanes, triallyl cyanurate polymers, triallyl isocyanurate polymers, certain silicones, and polymerizable prepolymers (e.g., prepolymers having ethylenic unsaturation, such as unsaturated polyesters, polyimides, etc.). Prepolymers include, for example, styrene, alpha-methylstyrene, vinyl toluene, chlorostyrene, acrylic acid, (meth)acrylic acid, (C 1~6 alkyl) acrylate, (C 1~6 It may be polymerized, copolymerized or crosslinked with reactive monomers such as alkyl)methacrylates, acrylonitrile, vinyl acetate, allyl acetate, triallyl cyanurate, triallyl isocyanurate or acrylamide.

[0023] Methods of forming the composite may include, but are not limited to, injection molding, reaction injection molding, lamination, extrusion, compression molding, calendaring, casting, etc. The composite may be free of void spaces.

[0024] The article may include Ru-Co2Z ferrite. The article may be an antenna or an inductor core. The article may be for use in frequencies in the 0.1-4 gigahertz range, or in the 0.5-2 gigahertz range. The article may be used in various devices operable in the ultra-high frequency range, such as shortwave or microwave antennas, filters, inductors, circulators, or phase shifters. The article may be operable at frequencies above 0.1 GHz, or above 0.3 GHz. Such articles may be used in commercial and military applications, weather radar, scientific communications, wireless communications, autonomous automobiles, aircraft communications, space communications, satellite communications, or surveillance.

[0025] As disclosed herein, the ferrite composition has the formula (Ba 3-x M x )Co2(M'Ru) y Fe 24-2y-z O 41 The ferrite composition may include a Ru-Co2Z ferrite of the formula: (wherein M is at least one of Sr, Pb, or Ca; M' is at least one of Co, Zn, Mg, or Cu; x is 1 to 3; y is greater than 0 to 2, or 0.001 to 2; and z is -4 to 4). M' may be at least Co. The ratio of Ru to M' may be 0.01 to 3. The ferrite composition may further include Bi2O3 in an amount of 0.2 to 5.0 weight percent, based on the total weight of the ferrite composition. The ferrite composition may have, in solid ceramic form, a magnetic permeability of 3.5 or greater at a frequency of 1 to 2 gigahertz. The ferrite composition may have, in solid ceramic form, a dielectric constant of 6 to 15 at a frequency of 1 to 2 gigahertz. The ferrite composition may have, in solid ceramic form, a magnetic loss tangent tanδ of 0.12 or less, or 0.08 or less at a frequency of 1 to 2 gigahertz. μ The ferrite composition, in solid ceramic form, may have a dielectric loss tangent tanδ of 0.01 or less, or 0.008 or less, at frequencies between 1 and 2 gigahertz. εThe composite may include the ferrite composition and a polymer. The article may include the ferrite composition or the composite. The article may be an antenna, a filter, an inductor, a circulator, or a phase shifter. The article may be a microwave antenna. The antenna may be capable of operating at frequencies of 0.1 gigahertz or greater, or 0.3 gigahertz or greater, or between 0.1 and 4 gigahertz.

[0026] A method of making a ferrite composition may include mixing ferrite precursor compounds including Fe, Ba, Co, and Ru; and sintering the ferrite precursor compounds in an oxygen atmosphere to form Ru-Co2Z ferrite. The ferrite precursor compounds may include BaCO3, MCO3, Co3O4, RuO2, and Fe2O3, where M is at least one of Sr, Pb, or Ca. The ferrite precursor compounds may include 5-20 weight percent BaCO3, 5-20 weight percent MCO3, 2-15 weight percent Co3O4, 0.1-10 weight percent RuO2, and 50-80 weight percent Fe2O3, all based on the total weight of the mixture. The sintering step may be performed at a sintering temperature of 1,000-1,300°C, or 1,200-1,250°C, for a sintering time of 1-20 hours, or 5-12 hours. The method may further include calcining the ferrite precursor compound in air prior to the sintering step.The method may further include mixing the ferrite precursor compound with a binder prior to the sintering step.The method may further include forming the ferrite precursor compound prior to the sintering step.

[0027] The following examples are provided to illustrate the present disclosure. The examples are merely illustrative and are not intended to limit devices made according to the present disclosure to the materials, conditions, or process parameters set forth therein. EXAMPLES

[0028] In the examples, the magnetic permeability of the obtained ferrite samples was measured by a vector network analyzer (VNA) using the Nicholson-Ross-Weir (NRW) method with a coaxial antenna at frequencies from 0.1 to 10 GHz.

[0029] (Examples 1 to 8) Preparation of Ru-Co2Z ferrite samples The Ru-Co2Z ferrite sample was prepared by the general formula (Ba 1.5 Sr 1.5 )Co2(CoRu) y Fe 22.4-2y O 41 The amount of ruthenium in the powder, y, was varied to form ferrite compositions as shown in Table 1. Ru-Co2Z ferrite was prepared by mixing appropriate amounts of BaCO3, SrCO3, Co3O4, Fe2O3, and RuO2 in a wet planetary mill to form a mixture. The mixture was calcined in air to a calcination temperature of 1,200°C for a soaking time of 4 hours to form ferrite. The ferrite was crushed and sieved through a 40 mesh screen. The coarse particles were ground in a wet planetary mill to form fine particles having a median D50 volumetric particle size of 0.5 to 10 micrometers. The fine particles were mixed with 0.5 to 5 weight percent poly(vinyl alcohol) based on the total amount of the particle mixture to form a particle mixture. The fine particle mixture was then compressed at a pressure of 1 metric ton per square centimeter to form toroidal grains having an outer diameter of 7 millimeters, an inner diameter of 3 millimeters, and a thickness of 3 to 3.5 millimeters. The toroidal grains were sintered for 10 hours at sintering temperatures of 1,200°C, 1,220°C, or 1,240°C in an oxygen atmosphere by flowing oxygen gas at a rate of 0.5 liters per minute using a ramp rate of 3°C per minute and a cooling rate of -3°C per minute.

[0030] [Table 1]

[0031] Various ferrite compositions were prepared with sintering temperatures and y values ​​as shown in Tables 2 and 3. The permeability (solid lines) and loss tangent (dashed lines) are shown as a function of frequency in Figures 1, 2, and 3, and the property values ​​for the different compositions are shown in Table 2. Note that in Figure 3, samples with asterisks are replicate samples. The permittivity (solid lines) and loss tangent (dashed lines) of several samples are shown as a function of frequency in Figure 4, and the property values ​​for the different compositions are shown in Table 3.

[0032] [Table 2]

[0033] The results show that increasing the amount of ruthenium significantly reduces the magnetic loss tangent while still maintaining a permeability, μ', of above 3 at 1-2 GHz. The results also show that simply by increasing the sintering temperature the permeability can be increased while the magnetic loss tangent is further reduced.

[0034] [Table 3]

[0035] Table 3 and FIG. 4 show that increasing the sintering temperature can increase the dielectric constant while maintaining a low dielectric tangent value.

[0036] (Examples 9 to 10) Preparation of Ru-Co2Z ferrite samples using one-step sintering process The Ru-Co2Z ferrite sample was treated with the general formula (Ba 1.5 Sr 1.5 )Co2(CoRu) y Fe 22.4-2y O 41The amount of ruthenium, y, in the powder was varied to form ferrite compositions as shown in Table 1. Ru-Co2Z ferrite was prepared by mixing appropriate amounts of BaCO3, SrCO3, Co3O4, RuO2, and Fe2O3 in a wet planetary mill to form a mixture. The particulate was mixed with 0.5 to 5 weight percent poly(vinyl alcohol) based on the total amount of the mixture to form a mixture. The mixture was then compressed at a pressure of 1 metric ton per square centimeter to form toroidal grains having an outer diameter of 7 millimeters, an inner diameter of 3 millimeters, and a thickness of 3 to 3.5 millimeters. The toroidal grains were sintered at a sintering temperature of 1,220°C or 1,240°C for 10 hours in an oxygen atmosphere using a ramp rate of 3°C per minute and a cooling rate of -3°C per minute, with oxygen gas flowing at a rate of 0.5 liters per minute.

[0037] Various ferrite compositions were prepared with sintering temperatures and y values ​​as shown in Tables 4 and 5. The magnetic permeability (solid line) and magnetic loss tangent (dashed line) are shown as a function of frequency in Figure 5, and the property values ​​for the different compositions are shown in Table 4. The dielectric constant (solid line) and dielectric loss tangent (dashed line) of some samples are shown as a function of frequency in Figure 6, and the property values ​​for the different compositions are shown in Table 5.

[0038] [Table 4]

[0039] [Table 5]

[0040] The results show that good permeability and magnetic loss tangent values ​​are maintained using a one-step sintering process.

[0041] (Examples 11 to 14) Preparation of composites containing ferrite compositions The Ru-Co2Z ferrite sample was treated with the general formula (Ba 1.5 Sr 1.5 )Co2(CoRu) y Fe 22.4-2y O 41 The amount of ruthenium, y, in the ferrite powder was varied to form ferrite compositions as shown in Table 1. Ru-Co2Z ferrite was prepared by mixing appropriate amounts of BaCO3, SrCO3, Co3O4, Fe2O3, and RuO2 in a wet planetary mill to form a mixture. The mixture was calcined to a calcination temperature of 1,200°C with a soaking time of 4 hours in air to form ferrite. The ferrite was crushed and sieved through a 100 mesh screen. The coarse particles were sintered in air at 1,240°C for 10 hours, ground in a wet planetary mill to form fine particles, and annealed at 900°C for 2 hours in oxygen flowing at a rate of 0.4 liters per minute to form ferrite powder. The ferrite powder had a median D50 particle size of 3 to 6 micrometers. The ferrite powder was mixed with paraffin wax to form a composite containing 40 volume percent ferrite powder and 60 volume percent paraffin wax. The composite was molded into a toroid with an outer diameter of 7 millimeters, an inner diameter of 3 millimeters, and a thickness of 2.5 millimeters, and the magnetic and dielectric properties were measured.

[0042] The magnetic properties are shown in Table 6, and the dielectric properties are shown in Table 7.

[0043] [Table 6]

[0044] [Table 7]

[0045] The results show good magnetic permeability and magnetic loss tangent values ​​for the composites containing ferrite particles.

[0046] The following are non-limiting aspects of the present disclosure.

[0047] Aspect 1 Formula: (Ba 3-x M x )Co2(M'Ru) y Fe 24-2y-z O 41 (wherein M is at least one of Sr, Pb, and Ca; M' is at least one of Co, Zn, Mg, and Cu; x is 1 to 3; y is greater than 0 and up to 2; and z is -4 to 4).

[0048] Aspect 2 The ferrite composition of embodiment 1, wherein y is 0.001 to 2.

[0049] Aspect 3 The ferrite composition of any one or more of the preceding embodiments, wherein M' is at least Co.

[0050] Aspect 4 The ferrite composition of any one or more of the preceding embodiments, wherein the ratio of Ru to M' is from 0.01 to 3.

[0051] Aspect 5 The ferrite composition of any one or more of the preceding embodiments, further comprising Bi2O3 in an amount of 0.2 to 5.0 weight percent, based on a total weight of the ferrite composition.

[0052] Aspect 6 2. The ferrite composition of any one or more of the preceding embodiments, in solid ceramic form, having a magnetic permeability of 3.5 or greater at frequencies of 1 to 2 gigahertz.

[0053] Aspect 7 2. The ferrite composition of any one or more of the preceding embodiments, in solid ceramic form, having a dielectric constant of 6 to 15 at frequencies of 1 to 2 gigahertz.

[0054] Aspect 8 In the form of a solid ceramic, the magnetic loss tangent tanδ is 0.12 or less, or 0.08 or less at frequencies between 1 and 2 gigahertz. μ 3. The ferrite composition of any one or more of the preceding embodiments, having the following structure:

[0055] Aspect 9 In the form of a solid ceramic, the dielectric loss tangent tanδ is 0.01 or less, or 0.008 or less at frequencies between 1 and 2 gigahertz. ε 3. The ferrite composition of any one or more of the preceding embodiments, having the following structure:

[0056] Aspect 10 20. An article comprising the ferrite composition of any one or more of the preceding embodiments.

[0057] Aspect 11 The article of embodiment 10, which is an antenna, a filter, an inductor, a circulator, or a phase shifter.

[0058] Aspect 12 The article of any one or more of aspects 10-11, which is a microwave antenna.

[0059] Aspect 13 The article of any one or more of aspects 10-12, wherein the antenna is operable at a frequency of 0.1 gigahertz or greater, or 0.3 gigahertz or greater, or 0.1-4 gigahertz.

[0060] Aspect 14 For example, a method of making a ferrite composition of any one or more of the preceding embodiments, comprising: mixing ferrite precursor compounds comprising Fe, Ba, Co, and Ru; and sintering the ferrite precursor compounds in an oxygen atmosphere to form Ru-CoZ ferrite.

[0061] Aspect 15 The method of embodiment 14, wherein the ferrite precursor compounds include BaCO3, MCO3, Co3O4, RuO2, and Fe2O3, where M is at least one of Sr, Pb, or Ca.

[0062] Aspect 16 16. The method of embodiment 15, wherein the ferrite precursor compound comprises 5 to 20 weight percent BaCO, 5 to 20 weight percent MCO, 2 to 15 weight percent CoO, 0.1 to 10 weight percent RuO, and 50 to 80 weight percent FeO, all based on a total weight of the mixture.

[0063] Aspect 17 17. The method of any one or more of aspects 14 to 16, wherein the sintering step is performed at a sintering temperature of 1,000 to 1,300° C. or 1,200 to 1,250° C. for a sintering time of 1 to 20 hours or 5 to 12 hours.

[0064] Aspect 18 The method of any one or more of embodiments 14-16, further comprising calcining the ferrite precursor compound in air prior to the sintering step.

[0065] Aspect 19 The method of any one or more of embodiments 14-18, further comprising mixing the ferrite precursor compound with a binder prior to the sintering step.

[0066] Aspect 20 The method of any one or more of embodiments 14-19, further comprising the step of forming a ferrite precursor compound prior to the sintering step.

[0067] Aspect 21 13. A composite comprising the ferrite composition of any one or more of the preceding embodiments.

[0068] The compositions, methods and articles may alternatively comprise, consist of, or consist essentially of any suitable materials, steps or components disclosed herein. The compositions, methods and articles may additionally or alternatively be designed to be free of, or substantially free of, any materials (or species), steps or components that are not otherwise essential to achieve the function or purpose of the compositions, methods and articles.

[0069] As used herein, "a," "an," "the," and "at least one" do not denote limitations of quantity and are intended to encompass both the singular and the plural, unless the context clearly indicates otherwise. For example, "an element" has the same meaning as "at least one element," unless the context clearly indicates otherwise. The term "combination" includes blends, mixtures, alloys, reaction products, and the like. Also, "at least one of" means that the list includes each element individually, as well as combinations of two or more elements of the list, and combinations of at least one element of the list with a similar element not listed.

[0070] The term "or" means "and / or" unless the context clearly dictates otherwise. Throughout this specification, references to "one embodiment," "another embodiment," "some embodiments," etc. mean that a particular element (e.g., a feature, structure, step, or characteristic) described in connection with that embodiment is included in at least one embodiment described herein and may or may not be present in other embodiments. Furthermore, it is to be understood that the described elements may be combined in any suitable manner in the various embodiments.

[0071] Unless specified to the contrary herein, all test standards are the latest standards in effect as of the filing date of this application or, if priority is claimed, the filing date of the earliest priority application in which the test standard appears.

[0072] The endpoints of all ranges directed to the same component or property are inclusive, independently combinable, and include all intermediate points and ranges. For example, a range of "up to 25% by volume, or 5-20% by volume" includes the endpoint and all intermediate points in the range "5-25% by volume," such as 10-23% by volume.

[0073] Unless otherwise defined, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.

[0074] All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term from this application contradicts or conflicts with a term from an incorporated reference, the term from this application takes precedence over the conflicting term from the incorporated reference.

[0075] While particular embodiments have been described, presently unanticipated or unanticipated alternatives, modifications, variations, improvements, and substantial equivalents may occur to applicant or others skilled in the art, and it is accordingly intended that the appended claims, as filed and as they may be amended, shall embrace all such alternatives, modifications, variations, improvements, and substantial equivalents.

Claims

1. formula: (BL 3-x M x )Co 2 (M'Ru) y Fe 24-2y-z O 41 (In the formula, M is at least one of Sr, Pb, or Ca; M' is at least one of Co, Zn, Mg, or Cu; x is 1 to 3; y is greater than 0 to 2; and z is -4 to 4.) Ru-Co 2 A ferrite composition comprising Z ferrite.

2. The ferrite composition according to claim 1, wherein y is 0.001 to 2.

3. The ferrite composition according to claim 1 or 2, wherein M' is at least Co.

4. Bi in an amount of 0.2 to 5.0 mass percent based on the total mass of the ferrite composition. 2 O 3 The ferrite composition according to claim 1 , further comprising:

5. A ferrite composition according to any one of claims 1 to 4, which in solid ceramic form has a magnetic permeability of 3.5 or greater at frequencies of 1 to 2 gigahertz.

6. A ferrite composition according to any one of claims 1 to 5, in solid ceramic form, having a dielectric constant of between 6 and 15 at frequencies between 1 and 2 gigahertz.

7. In the form of a solid ceramic, at frequencies between 1 and 2 gigahertz, a magnetic loss tangent tan δ of 0.12 or less, or 0.08 or less. μ The ferrite composition according to claim 1 , wherein

8. In the form of a solid ceramic, at frequencies between 1 and 2 gigahertz, a dielectric loss tangent tan δ of 0.01 or less, or 0.008 or less. ε The ferrite composition according to claim 1 , wherein

9. A composite comprising the ferrite composition according to any one of claims 1 to 8 and a polymer.

10. An article comprising the ferrite composition according to any one of claims 1 to 8 or the composite according to claim 9.

11. 11. The article of claim 10 which is an antenna, a filter, an inductor, a circulator, or a phase shifter.

12. 12. The article of claim 10 or 11, which is a microwave antenna.

13. 13. The article of any one of claims 10 to 12, which is an antenna operable at frequencies of 0.1 gigahertz or more, or 0.3 gigahertz or more, or 0.1 to 4 gigahertz.

14. A method for making the ferrite composition of any one of claims 1 to 8, comprising the steps of: Mixing ferrite precursor compounds containing Fe, Ba, Co and Ru; and The ferrite precursor compound was sintered in an oxygen atmosphere to obtain Ru-Co. 2 Step of forming Z ferrite A method comprising:

15. The ferrite precursor compound is BaCO 3 , M.C.O. 3 , Co 3 O 4 , RuO 2 and Fe 2 O 3 15. The method of claim 14 comprising: wherein M is at least one of Sr, Pb, or Ca.

16. The ferrite precursor compound is 5 to 20 weight percent BaCO 3 , 5 to 20 weight percent MCO 3 , 2 to 15 mass percent Co 3 O 4 , 0.1 to 10 mass percent RuO 2 and 50 to 80 mass percent Fe 2 O 3 16. The method of claim 15, comprising:

17. The method according to any one of claims 14 to 16, wherein the sintering step is carried out at a sintering temperature of 1,000 to 1,300°C, or 1,200 to 1,250°C, for a sintering time of 1 to 20 hours, or 5 to 12 hours.

18. 18. The method of any one of claims 14 to 17, further comprising the step of calcining the ferrite precursor compound in air prior to the sintering step.

19. 19. The method of any one of claims 14 to 18, further comprising the step of mixing the ferrite precursor compound with a binder prior to the sintering step.

20. 20. The method of any one of claims 14 to 19, further comprising the step of forming a ferrite precursor compound prior to the sintering step.

Citation Information

Patent Citations

  • Metal oxide magnetic substance and magnetic film

    JP1986089604A

  • Z-type hexagonal ferrite

    JP2015030630A

  • Modified z-type hexagonal ferrite materials with enhanced resonant frequency

    JP2017071511A

  • Co2Z-type ferrite composite material for use of extremely high frequency antenna

    JP2017528403A

  • Enhanced hexagonal ferrite material and methods of preparation thereof

    US20130292602A1